PERAN KOMUNIKASI ISLAM DALAM MENYIKAPI ISU TERORISME DI INDONESIA - Hamiruddin Hamiruddin (240-540X)
Terrorism and radicalism are one of the most important discussion topics that are often the object of discussion among politicians and experts. Both of these issues in the world stage are strongly influenced by information from various media, especially Western media in general who have identified Islam as a terrorist religion. This is where the importance of the existence and role of Islamic communication to re-knit public opinion that views Islam as a terrorist religion. Islamic communication must be at the forefront in providing answers to various negative stigmatization of Islam in general both in the international and national regions in particular.